A survey of physicians' attitudes toward uterotonic administration in parturients undergoing cesarean section. (2nd December 2018) - Orbach-Zinger, Sharon; Einav, Sharon; Yona?, Assaf; Eidelman, Leonid A.; Fein, Shia; Davis, Atara; Ioscovich, Alexander
Abstract: Objective: Oxytocin is globally accepted as first-line treatment for prevention of post-partum hemorrhage. However, there is wide variability in its use in clinical practice. In this study, we aimed to evaluate obstetricians and anesthesiologists attitudes towards uterotonic practices in Israel. Study design: The current survey was designed to study the preferences of obstetricians and anesthesiologists in seven University hospitals regarding the type, dose, and mode of administration of uterotonic drugs, as well as their knowledge regarding the side effects of these drugs. Results: A total of 429 anesthesiologists and obstetricians were approached for participation. Three hundred and ninety-one physicians responded: 48% obstetricians and 52% anesthesiologists. Variations in oxytocin practices were significantly different between obstetricians and anesthesiologists in primary CS ( p < .01). Nonetheless, both cohorts reported using an aggressive approach, administering an IV bolus of 5 or 10 units. In repeat CS no significant difference was demonstrated ( p = .065). Additionally, we found increased treatment with Methergine as a second-line uterotonic management. Conclusions: Our study confirmed significant variability in attitudes towards uterotonic management amongst obstetricians and anesthesiologists. Our study highlights the importance of implementing national guidelines for oxytocin use, which will hopefully reduce the use of high bolus dosage usage, thereby increasing patient safety.